(untitled) (Journal of the Institute of Agriculture and Animal Science, 2025)
Crop residues are valuable natural resources in the paddy-wheat cropping system, and their proper management can enhance the physical, chemical, and biological properties of soil. Burning of crop residues is one of the major problems associated with paddy-wheat cropping system in western Terai of Nepal. In order to evaluate the different crop residue management practices and their effects on crop yield and soil organic matter under the paddy-wheat cropping system, a field experiment was conducted at the National Wheat Research Program, Bhairahawa, Rupandehi, Nepal between 2019 to 2021. The experiment was conducted in the split-plot design with three main-plot treatments of residue management (residue removal, residue incorporation, and residue burning) and three sub-plot fertilizer levels (control, recommended dose of NPK, and 125% of the recommended doses of NPK), replicated three times. The combined analysis of data over three years revealed that the residue management had significantly influenced the grain yield. The highest grain yield (3648 kg ha-1) was recorded from the residue incorporation. Similarly, fertilizer levels significantly affected both the yield and yield components of paddy, with the highest mean grain yield (4173 kg ha-1) obtained from the 125% NPK of the recommended dose. Although residue management and fertilizer levels did not significantly influence overall soil fertility status, residue management had a significant effect on soil organic matter content. The highest organic matter content (2.23%) was observed in the residue incorporation, while the lowest (1.85%) was recorded from the residue burning. The interaction between residue management and fertilizer level had no significant effect on grain yield or soil fertility status.